KAJIAN TEORITIS PENTINGNYA STANDAR BAKU MUTU KEUANGAN SEBUAH LEMBAGA - Fajarwati, Diana (Fakultas Ekonomi Universitas Islam 45, 2009)
Financial reporting is information that is used as the basis for decision making, therefore the financial statements must be accurate and reliable. The financial statements consist of statements Balance Sheet, profit and loss, and report changes in capital The income statement reports income and expenses, which according to the economic concept of income must be fought is the highest while the lowest-cost rendahnay. Better cost control must implement the standard fee so it can determine the difference from the established standards